Pengaruh Cash Flow, Leverage, Financial Constraint Terhadap Investasi Di Indonesia Pada Perusahaan Sektor Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018 - Perwitasari, Diah (Akmenika: Jurnal Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of Cash Flow, Leverage, and Financial Constraint on Investment on Consumerss Good companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The sampling technique is purposive sampling. Samples were obtained from 23 Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. Based on the results of data analysis shows that Cash Flow and Leverage have a negative and significant effect on Investment, Financial Constraint have a negative and no significant effect on Investment. Together Cash Flow, Leverage, and Financial Constraint on Investment have a positive and significant effect on Investment.Keywords: Cash Flow, Leverage, Financial Constraint, and Investment.